Respuesta :
First, subtract 6 from both sides. You have -12-6=2/3x.
-12-6 equals -18
-18= 2/3x
To get x by itself, you have to do the opposite operation. Divide -18 by
2/3. To do that, you do -18/1 ÷ 2/3. To divide fractions, you switch the two numbers on the second fraction. Then switch the × to ÷.
Now, you have -18/1 * 3/2 which equals -27.
x= -27
Hope this helps! :D
-12-6 equals -18
-18= 2/3x
To get x by itself, you have to do the opposite operation. Divide -18 by
2/3. To do that, you do -18/1 ÷ 2/3. To divide fractions, you switch the two numbers on the second fraction. Then switch the × to ÷.
Now, you have -18/1 * 3/2 which equals -27.
x= -27
Hope this helps! :D
For the equation, x would equals -27.
2/3x + 6 = -12
- 6 = -6
3/2 • 2/3x = -18 • 3/2
x = -27
2/3x + 6 = -12
- 6 = -6
3/2 • 2/3x = -18 • 3/2
x = -27